Technical newness: Putting a spotlight on its dynamic nature and effects - Katrin Talke; Sebastian Müller; Jaap E. Wieringa (ZBW - Leibniz Information Centre for Economics, 2024)
Differentiating products by means of novel technical features is an accepted approach to achieving and retaining long-term success. So far, innovation research has treated technical newness as a static concept. In this paper, we introduce a dynamic perspective and enhance the technical newness concept in three ways. First, we acknowledge that customers become accustomed to a product and perceive it as less new as time goes by. Second, we consider product updates that introduce new features and functionalities across a product's life cycle. Third, we uncover how technical newness affects the sales performance of new products over time. We track 175 cars over their life cycle, and find that the effect of technical newness takes an inverted-U shape. Our results imply that a dynamic perspective is crucial both when assessing a product's technical newness and when analyzing its performance impact.
Keywords: 330; Technology life cycle; Technological Change; Management of Technological Innovation